Brain activity monitoring by compressed spectral array during deep hypothermic circulatory arrest in acute aortic dissection surgery - Urbanowicz, Tomasz K. (Kardiochir Torakochirurgia Pol, 2014)
INTRODUCTION: Monitoring the central nervous system during aortic dissection repair may improve the understanding of the intraoperative changes related to its bioactivity. AIM: The aim of the study was to evaluate the influence of deep hypothermia on intraoperative brain bioactivity measured by the compressed spectral array (CSA) method and to assess the influence of the operations on postoperative cognitive function. MATERIAL AND METHODS: The study enrolled 40 patients (31 men and 9 women) at the mean age of 60.2 ± 8.6 years, diagnosed with acute aortic dissection. They underwent emergency operations in deep hypothermic circulatory arrest (DHCA). During the operations, brain bioactivity was monitored with the compressed spectral array method. RESULTS: There were no intraoperative deaths. Electrocerebral silence during DHCA was observed in 31 patients (74%). The lowest activity was observed during DHCA: it was 0.01 ± 0.05 nW in the left hemisphere and 0.01 ± 0.03 nW in the right hemisphere. The postoperative results of neurological tests deteriorated statistically significantly (26.9 ± 1.7 points vs. 22.0 ± 1.7 points; p < 0.001), especially among patients who exhibited brain activity during DHCA. CONCLUSIONS: The compressed spectral array method is clinically useful in monitoring brain bioactivity during emergency operations of acute aortic dissections. Electrocerebral silence occurs in 75% of patients during DHCA. The cognitive function of patients deteriorates significantly after operations with DHCA.